Concurrent improvement and deterioration of epilimnetic water quality in an oligotrophic lake over 37 years. (31st October 2019) - Hintz, William D.; Schuler, Matthew S.; Borrelli, Jonathan J.; Eichler, Lawrence W.; Stoler, Aaron B.; Moriarty, Vincent W.; Ahrens, Laurie E.; Boylen, Charles W.; Nierzwicki‐Bauer, Sandra A.; Relyea, Rick A.
Abstract: Single‐lake studies offer an opportunity for understanding, predicting, and mitigating local or regional threats to lake ecosystems. Our goal was to understand how concurrent environmental stressors such as climate change, eutrophication, and salinization affect long‐term lake water quality. We report epilimnetic changes in 18 water‐quality parameters collected at seven sites from 1980 to 2016 in Lake George, a large oligotrophic lake in the Adirondack Park, New York, USA. Improvements and deteriorations in water quality occurred over 37 years. We observed a 32% increase in chlorophyll a associated with an increase in orthophosphate, but not total phosphorus or a warming epilimnion (0.05°C/year). Salinization from road deicing salts contributed to the largest deterioration in water quality. However, chloride concentrations and the current rate of increase are low enough that few ecological impacts are likely to occur over the next few decades. Increasing calcium concentrations were not high enough to facilitate the persistence of invasive species in the lake such as zebra mussels ( Dreissena polymorpha ) but are sufficient for Asian clams ( Corbicula fluminea ) and the spiny water flea ( Bythotrephes longimanus ). Similar to other lakes, environmental legislation has supported recovery from acidification, indicated by reduced sulfate and nitrate, and increased alkalinity and pH. Declines in water quality were minor relative to other lakes, suggesting that decades of tourism and development occurred without major deterioration in water quality, but management efforts are needed to curb salinization in the Lake George watershed, particularly as it relates to sodium concentrations to prevent a loss of drinking water quality.